Paesaggio: didattica, ricerche e progetti (1997-2007) (2007)
A collection of essays such as this is intended primarily as evidence of a disciplinary process, a path that is moreover similar to that pursued in other Italian universities, while also being unique in its evolution and as specific as every experience must be. Ten years of scientific and educational work on the landscape were deserving of comment, and we have made this in the only way we know: in writing. Hence there is no celebratory intention. It is simply one of many ways of making a sort of self-analysis, of gaining a deeper insight into ourselves and expounding our experience to others, explaining what we have produced, how we did it and what the results were, with the aim of putting our experience at the disposal of those who deal with the same disciplinary areas or with analogous issues.